2001
DOI: 10.1089/08977150152693683
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylaspartate Reduction as a Measure of Injury Severity and Mitochondrial Dysfunction Following Diffuse Traumatic Brain Injury

Abstract: N-Acetylaspartate (NAA) is considered a neuron-specific metabolite and its reduction a marker of neuronal loss. The objective of this study was to evaluate the time course of NAA changes in varying grades of traumatic brain injury (TBI), in concert with the disturbance of energy metabolites (ATP). Since NAA is synthesized by the mitochondria, it was hypothesized that changes in NAA would follow ATP. The impact acceleration model was used to produce three grades of TBI. Sprague-Dawley rats were divided into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
135
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(157 citation statements)
references
References 84 publications
17
135
0
5
Order By: Relevance
“…In this study, patients were imaged on average 6 Ϯ 4 days following injury, with some as long as 16 days after injury. Animal models have shown that metabolites such as Cho and mI increase soon after injury (38) whereas, NAA associated with neuronal dysfunction may remain depressed for days to weeks depending on the severity of injury (41) and may be permanent if neuronal loss has occurred (39). The time course for metabolic changes following TBI is not well established in humans and may vary by age as well as injury severity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients were imaged on average 6 Ϯ 4 days following injury, with some as long as 16 days after injury. Animal models have shown that metabolites such as Cho and mI increase soon after injury (38) whereas, NAA associated with neuronal dysfunction may remain depressed for days to weeks depending on the severity of injury (41) and may be permanent if neuronal loss has occurred (39). The time course for metabolic changes following TBI is not well established in humans and may vary by age as well as injury severity.…”
Section: Discussionmentioning
confidence: 99%
“…After anaesthesia, a metal disk was fixed onto the central portion of the skull, between the coronal and lambdoid sutures, to prevent skull fracture and to homogenously distribute the force acting at the time of impact. Mild or severe TBI were induced by dropping a cumulative weight of 450 g from 1 or 2 m height and knowing to cause, respectively, a mTBI or a sTBI either histopathologically or biochemically 34, 35, 36, 37, 38. At 6, 12, 24, 48 and 120 hrs from injury, rats were again anaesthetized ( n = 6 for each time‐point in both groups of injured animals) and then immediately killed.…”
Section: Methodsmentioning
confidence: 99%
“…However, animal studies of moderate to severe TBI have shown more rapid declines in NAA levels which were paralleled by decreases in ATP levels. Using HPLC analyses of brain extracts, Signoretti and colleagues reported significant and concomitant drops in NAA and ATP within 10 minutes of injury, and partial recovery of both compounds by 5 days in less severe injuries (Signoretti et al, 2001). In more severe TBI injuries, and those exacerbated by hypoxia-hypotension, recovery of NAA and ATP levels was not observed.…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%